The expression of LINE1‐MET chimeric transcript identifies a subgroup of aggressive breast cancers. Issue 11 (4th October 2018) - Miglio, Umberto; Berrino, Enrico; Panero, Mara; Ferrero, Giulio; Coscujuela Tarrero, Lucia; Miano, Valentina; Dell'Aglio, Carmine; Sarotto, Ivana; Annaratone, Laura; Marchiò, Caterina; Comoglio, Paolo M.; De Bortoli, Michele; et al.
Abstract : Demethylation of the long interspersed nuclear element (LINE‐1; L1) antisense promoter can result in transcription of neighboring sequences as for the L1‐ MET transcript produced by the L1 placed in the second intron of MET . To define the role of L1‐ MET, we investigated the sequence and the transcription of L1‐ MET in vitro models and heterogeneous breast cancers, previously reported to show other L1‐derived transcripts. L1‐ MET expressing cell lines were initially identified in silico and investigated for L1‐ MET promoter methylation, cDNA sequence and cell fraction mRNA. The transcriptional level of L1‐ MET and MET were then evaluated in breast specimens, including 9 cancer cell lines, 41 carcinomas of different subtypes, and 11 normal tissues. In addition to a L1‐ MET transcript ending at MET exon 21, six novel L1‐ MET splice variants were identified. Normal breast tissues were negative for the L1‐ MET expression, whereas the triple‐negative breast cancer (TNBC) and the high‐grade carcinomas were enriched with the L1‐ MET mRNA ( p = 0.005 and p = 0.018, respectively). In cancer cells and tissues the L1– MET expression was associated with its promoter hypomethylation ( ρ = −0.8 and −0.9, respectively). No correlation was found between L1‐ MET and MET mRNA although L1‐ MET expressing tumors with higher L1‐ MET/MET ratio were negative for the MET protein expression ( p = 0.006). Besides providing the first identification and detailed description of L1‐ MET in breast cancer, we clearly demonstrate that higher levels of this transcript specifically recognize a subset of more aggressive carcinomas, mainly TNBC. We suggest the possible evaluation of L1‐ MET in the challenging diagnosis of early TNBCs. Abstract : What's new? The transposable element L1 can generate some troublesome transcripts, occasionally leading to cancer. Here, the authors set out to thoroughly characterize the L1‐ MET transcript and investigate its role in breast cancer. They identified numerous cell types expressing L1‐ MET, including a variety of cancer subtypes. They found that L1‐ MET transcripts are present in breast cancers but not in untransformed breast cells, with highest levels occurring in the more aggressive tumors, particularly triple‐negative cancers.